3mx-9y=2(m+2b)

Simple and best practice solution for 3mx-9y=2(m+2b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3mx-9y=2(m+2b) equation:


Simplifying
3mx + -9y = 2(m + 2b)

Reorder the terms:
3mx + -9y = 2(2b + m)
3mx + -9y = (2b * 2 + m * 2)
3mx + -9y = (4b + 2m)

Solving
3mx + -9y = 4b + 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
3mx + -2m + -9y = 4b + 2m + -2m

Reorder the terms:
-2m + 3mx + -9y = 4b + 2m + -2m

Combine like terms: 2m + -2m = 0
-2m + 3mx + -9y = 4b + 0
-2m + 3mx + -9y = 4b

Add '9y' to each side of the equation.
-2m + 3mx + -9y + 9y = 4b + 9y

Combine like terms: -9y + 9y = 0
-2m + 3mx + 0 = 4b + 9y
-2m + 3mx = 4b + 9y

Reorder the terms:
-4b + -2m + 3mx + -9y = 4b + 9y + -4b + -9y

Reorder the terms:
-4b + -2m + 3mx + -9y = 4b + -4b + 9y + -9y

Combine like terms: 4b + -4b = 0
-4b + -2m + 3mx + -9y = 0 + 9y + -9y
-4b + -2m + 3mx + -9y = 9y + -9y

Combine like terms: 9y + -9y = 0
-4b + -2m + 3mx + -9y = 0

The solution to this equation could not be determined.

See similar equations:

| x-7=144 | | 4s^2+16s-as-4a= | | 2/3(3/5) | | (5/6)t+4=(1/6)t-2 | | 13x+3x-5=27 | | .0825t^2-.886t+1.752=0 | | 5x-15=x+25 | | -x^2+11=0 | | -8+x/8=-12 | | 6(6x+5)=-390 | | (10)+c^3/3=c^3/(3)+10 | | 6x+3=4x+7 | | 3x^2+5x+343=0 | | 11x-2(4x-6)=18 | | 2-20q-3q+12=5+4q+15 | | 2x+40=6x+8 | | 3q+6+2q+3=13q+19-3q | | 3k=7k+12 | | (2x+40)+(6x+8)=180 | | 1.7a+3.5=3.2a+11 | | 0.73+0.19t=2.29t-0.11 | | 1-2n=5n+1 | | 3p+4=5p-0 | | (9x+6)+(6x+9)=180 | | 5y-5+y+21=7y+20-3y | | -2/15(w+15)-1/5(3w-10)=2/3 | | 12y-6=4y+1 | | 7a-18=3a-2 | | -0.5x+0.8x+8=-7 | | 5(x+1)+8=2x-4(3x+2) | | -1/5(w+5)-1/4(5w+16)=4/5 | | 4sin^2x-2=0 |

Equations solver categories